Inequality Trends, Causes, Consequences, Relevant Policies (International Papers in Political Economy, 2018)
This book is the fifteenth volume in the renowned International Papers in Political Economy (IPPE) series which explores the latest developments in political economy. Containing contributions by experts in the field, this book focuses on topics that address the ongoing debate of inequalities in economic systems. Inequality has been considered a problem by many academics and policy makers for a long time now and recently here has been some evidence of increasing inequalities in society. Contributors to this book focus on the causes and consequences of inequality along with the importance of tackling inequality and recommend potential policies to reduce it, for example tax reforms. The book covers different aspects of inequality - from income to gender - and explores links between inequality and economic growth, and financialisation and financial crisis.